2011
DOI: 10.1111/j.1365-263x.2011.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary flow rate and oral findings in Prader–Willi syndrome: a case‐control study

Abstract: BACKGROUND. Prader-Willi syndrome (PWS) is a rare complex multisystemic genetic disorder. AIM. The objective of this study was to provide a systematic assessment of whole saliva secretion and oral manifestations associated with PWS. DESIGN. Fifty individuals (5-40 years) with PWS and an age- and sex-matched control group were included. Whole saliva was collected. All participants underwent an anamnestic interview. Radiological and dental clinical examinations were carried out to identify hypodontia, dental car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 25 publications
1
33
1
1
Order By: Relevance
“…However, found no significant difference between the risk of caries in individuals with PWS and in healthy patients [22]. In the present study, no significant differences were found regarding the caries indices between the populations, though caries were more frequent in individuals with PWS.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, found no significant difference between the risk of caries in individuals with PWS and in healthy patients [22]. In the present study, no significant differences were found regarding the caries indices between the populations, though caries were more frequent in individuals with PWS.…”
Section: Discussioncontrasting
confidence: 82%
“…As for the facial phenotype, patients with PWS usually present a narrow forehead, elongated almond-shaped eyes with ascending oblique palpebral fissures, and a triangular mouth with commissures facing downwards and thin upper lip [1,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Prader-Willi syndrome (PWS) is a complex genetic disorder resulting from failed expression of paternally inherited genes on chromosome 15q11-13. 101 Saeves et al 101 demonstrated that in PWS patients saliva presents extremely thick and sticky; it is possible that the protein secretion in salivary glands may be functioning properly or even be overexpressed, whereas fluid secretion is reduced.…”
Section: Genetic Disordersmentioning
confidence: 98%
“…Decreased salivary flow rates [24] and increased amounts of salivary ions and proteins have also been reported [20,21]. Dental caries [25-28], enamel defects [27-31] and poor oral hygiene [27,28] have been described in case reports.…”
Section: Introductionmentioning
confidence: 99%